Ophthalmological factors influencing visual asthenopia as a result of viewing 3D displays. Issue 11 (5th September 2012) - Wee, Sung wook; Moon, Nam Ju; Lee, Won Ki; Jeon, Sohee
Abstract : Aims: To identify ophthalmological factors influencing asthenopia as a result of viewing three-dimensional (3D) displays. Methods: Thirty adult subjects without ophthalmological abnormality watched the same 3D displays for 30 min. Each subject's near point of accommodation (NPA) and convergence (NPC), amplitude of fusional convergence and divergence, stereopsis, tear break-up time and temperature of ocular surface, and angle of phoric deviation were measured before and after viewing the 3D displays. In addition, a survey for subjective symptoms was conducted immediately following the viewing of the 3D displays. The above mentioned experiments were performed equally with two-dimensional (2D) displays in the same 30 subjects for detection of innate influence of 3D displays. Results: The NPA and NPC in the subjects were significantly altered after watching the 3D displays (p<0.05) as compared with 2D displays. In addition, all of the 10 subjective symptoms measured were significantly increased after watching 3D displays (p<0.05). Conclusions: Accommodation and binocular vergence are predominant ophthalmological factors that may influence asthenopia significantly following the viewing of 3D displays. Subjective visual discomfort also significantly increased following the viewing of 3D displays. And there is the need for more detailed evaluation for detecting the practically related factors with asthenopia.